Why do We Know So Much and Yet So Little? A Scoping Review of Willingness to Pay for Human Excreta Derived Material in Agriculture - Gwara, Simon; Wale, Edilegnaw; Odindo, Alfred; Chris, Buckley (Sustainability, 2020)
Challenges associated with rapid population growth, urbanization, and nutrient mining have seen increased global research and development towards ‘waste to wealth’ initiatives, circular economy models, and cradle-to-cradle waste management principles. Closing the nutrient loop through safe recovery and valorization of human excreta for agricultural use may provide a sustainable method of waste management and sanitation. Understanding the market demand is essential for developing viable waste management and sanitation provision business models. The pathways and processes for the safe recovery of nutrients from human excreta are well-documented. However, only anecdotal evidence is available on the willingness to pay for human excreta-derived material in agriculture. This review closes this gap by identifying and synthesizing published evidence on farmers’ willingness to pay for human excreta-derived material for agricultural use. The Scopus and Web of Science search engines were used to search for the literature. The search results were screened, and the data were extracted, charted, and synthesized using the DistillerSR web-based application. The findings show that understanding willingness to pay for human excreta-derived material is still a nascent and emerging research area. Gender, education, and experience are common factors that influence the farmers’ willingness to pay. The findings show that pelletization, fortification, labeling, packaging, and certification are essential attributes in product development. The wide-scale commercialization can be achieved through incorporation of context-specific socioeconomic, religious and cultural influences on the estimation of willingness to pay. Promoting flexible legislation procedures, harmonization of regional legislations, and creating incentives for sustainable waste recovery and reuse may also promote the commercialization of circular nutrient economy initiatives. More empirical studies are required to validate willingness to pay estimates, especially using the best practice for conducting choice experiments.